Sampled grating DBR laser as a spectroscopic source in multigas detection at 1.52-1.57um - HEGARTY, JOHN (My University, 2001)
The first application is reported of multigas sensing using a widely tuneable sampled grating DBR laser with a tuning range 1520⩽?⩽1570 nm. The laser diode consists of four independently biased sections, two sampled gratings, a phase section and a gain section. Setting the laser emission wavelength within its broad tuning range is achieved by tuning the front and back grating mirrors. Three gases H2S, C2H2 and CO2 with absorption features within the 30 nm tuning range of the device were targeted and successfully detected. In addition, minimum detection limits were estimated using wavelength modulation spectroscopy. Initial results demonstrate the value of this device as a light source in absorption spectroscopy based multigas detection systems
PUBLISHED
Keywords: spectrochemical analysis